2017
DOI: 10.1371/journal.pone.0187207
|View full text |Cite
|
Sign up to set email alerts
|

Nasal carriage rate and antibiotic susceptibility pattern of Neisseria meningitidis in healthy Ethiopian children and adolescents: A cross-sectional study

Abstract: BackgroundCommunity nasal meningococcal carriage rates are high across Africa. Meningococcal infections are major causes of morbidity and mortality in the continent; especially among children and adolescents. This study aimed to determine the prevalence of nasal carriage and antibiotic susceptibilities of meningococcal isolates from healthy Ethiopian children and adolescents.MethodA cross-sectional study was conducted in one of the sub-cities of Addis Ababa, Ethiopia. Nasal swabs were collected and processed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 10 publications
6
17
8
1
Order By: Relevance
“…In contrast, our study had less carriage rate compared to three local studies conducted at Gondar university hospital (2019 CSF samples) in the year 2011 to 2013 with 18.4% prevalence [24], Addis Ababa (240 nasal swabs) with 20.4% carriage rate [8] and bacterial meningitis surveillance in Ethiopia, 2012-2013 (139 CSF samples) with 19.4% prevalence rate [25].…”
Section: Discussioncontrasting
confidence: 72%
“…In contrast, our study had less carriage rate compared to three local studies conducted at Gondar university hospital (2019 CSF samples) in the year 2011 to 2013 with 18.4% prevalence [24], Addis Ababa (240 nasal swabs) with 20.4% carriage rate [8] and bacterial meningitis surveillance in Ethiopia, 2012-2013 (139 CSF samples) with 19.4% prevalence rate [25].…”
Section: Discussioncontrasting
confidence: 72%
“…Twenty papers were identified which described meningococcal carriage surveys conducted in nine African meningitis belt countries and reported since 2007 [4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Sixteen of these surveys were conducted prior to the deployment of the group A meningococcal conjugate vaccine (MenAfriVac â ).…”
Section: Resultsmentioning
confidence: 99%
“…Risk factors for carriage of N. meningitidis. Six studies conducted by independent groups of investigators reported on risk factors for the prevalence of pharyngeal carriage of N. meningitidis and one study investigated risk factors for acquisition (Table 2) [6,9,18,22,23]. Age was a strong risk factor for carriage, with the prevalence of carriage peaking in those aged 5-14 years in nearly all surveys.…”
Section: Methodsmentioning
confidence: 99%
“…In Ethiopia, a major epidemic was recorded in 2001with 6964 cases and 330 deaths followed by another epidemic during 2003-2004 with 3326 cases and 160 deaths from all regions of the country [7]. The study conducted in Addis Ababa, Ethiopia showed that the prevalence of N. meningitidis among elementary school children was 20.4% [8].…”
Section: Introductionmentioning
confidence: 99%